Mechanical and Histological Characteristics of Phasix™ ST Mesh in a Porcine Model of Hernia Repair. Issue 2 (1st February 2022) - Deeken, Corey R.; Gagne, Darcy H.; Badhwar, Amit
Abstract: Purpose: The objective of this study was to determine mechanical and histological properties of Phasix™ ST Mesh in various defect sizes and characterize the tissue replacing Phasix™ ST Mesh in a porcine model of ventral hernia repair. Methods: Simulated hernia defects were surgically created in the midline of twenty-four (n = 24) Yucatan pigs. Treatment groups included 8 cm defect sutured closed (buttress) and unclosed 4 cm and 8 cm defect groups. Phasix™ ST Mesh (15 cm diameter circle) was implanted laparoscopically and fixated circumferentially with SorbaFix™ Absorbable Fixation System fasteners. The repair sites underwent mechanical, molecular weight, and histological evaluation at 48 and 72 weeks postimplantation. Results: Mechanical testing of Phasix™ ST Mesh-repaired sites revealed similar strengths at both time points for all three repair types, p  > 0.05 in all cases (48 weeks: 142.4 ± 6.0 N, 142.3 ± 16.5 N, and 168.8 ± 38.5 N; 72 weeks: 110.0 ± 18.3 N, 138.6 ± 42.2 N, and 160.6 ± 42.0 N for 4 cm defect, 8 cm defect, and 8 cm buttress, respectively. mean ± SEM) No significant differences were observed over time except at 72 weeks postimplantation when the 4 cm defect group exhibited significantly lower strength than the T0 strength of Phasix™ ST Mesh (204.6 ± 5.0 N, p  < 0.05). The molecular weight of Phasix™ ST Mesh decreased over time, regardless of repair type. Histological analysis showed comparable mature collagen/fibrovascular tissue around and within the Phasix™ ST Mesh interstices, including the segment of mesh overlying the defect. Conclusion: Phasix™ ST Mesh-repaired sites exhibited similar mechanical strengths and histological properties across all defect sizes in this porcine model.